Chronic Kidney Disease: Phosphorus and Your Diet - Nancy J. Gal; Lauren Headrick; Kate Bennett; Wendy J. Dahl (EDIS)
Phosphorous is an essential mineral necessary for the formation of bones and teeth, but also for kidney function and the regulation of muscle contractions, heartbeat, and nerve transmission. High blood levels of phosphorus may lead to adverse effects on bone, kidney, and heart health. When there is too much phosphorus in the blood, the body reacts by leaching calcium from the bones. This can be especially dangerous for those with Chronic Kidney Disease. This 4-page fact sheet discusses the relationship between Chronic Kidney Disease and Phosphorous intake, examining foods that are high in phosphorous and ways to manage phosphorous levels. Written by Nancy J. Gal, Lauren Headrick, Kate Bennett, and Wendy J. Dahl, and published by the Food Science and Human Nutrition Department, December 2015.